Hyperboloid Space Frames for Tower Structures - Levinton, Zusse (Engineering Journal, 1967)
In recent years the quest for esthetics in structural design has resulted in a number of new forms, utilizing shells, folded plates and other sophisticated shapes in reinforced concrete and metals. Rather pleasing effects have been achieved by exposing the structural framing on the exterior of building walls in checkered and diamond patterns. In the design of towers, graceful shapes and patterns of framing have been obtained by following the geometry of hyperboloids and other curved surfaces. While glamour, display and advertisement may be the factors inspiring some lavish architecture, there is still a need for esthetic treatment of more prosaic structures serving industrial and utilitarian purposes. One problem recognized by many architects and engineers is the water tower or elevated tank of conventional utilitarian design, an uninspiring sight at its best, and more often a blot on the landscape and a blight to the neighborhood. More attention is being given to improvement in appearance of water towers. Generally, better architectural treatment involves greater costs. More pleasing shapes of the tank proper, such as spheres and spheroids are not costly in themselves. The supporting tower structure, however, is more of a problem. Among recent designs, esthetic solutions are provided by rigid frames of steel or concrete, by metal shells as main supporting structure or as cover for interior framing, and by massive architectural masonry.